2013
DOI: 10.3390/nu5051585
|View full text |Cite
|
Sign up to set email alerts
|

Is Dietitian Use Associated with Celiac Disease Outcomes?

Abstract: A gluten-free diet (GFD) is the treatment for celiac disease (CD), but due to its complexity, dietitian referral is uniformly recommended. We surveyed patients with CD to determine if dietitian use is associated with quality of life, symptom severity, or GFD adherence. The survey utilized three validated CD-specific instruments: the CD quality of life (CD-QOL), CD symptom index (CSI) and CD adherence test (CDAT). Four hundred and thirteen patients with biopsy-proven CD were eligible for inclusion. The majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 24 publications
4
38
1
1
Order By: Relevance
“…Currently, the Celiac Dietary Assessment tool (CDAT) is the most widely used scoring system. The CDAT is a seven-item questionnaire that has been used and validated in six studies to date, involving 1855 patients (35,44,(46)(47)(48)(49) . The CDAT has yet to be compared to histology for adherence but was found to correlate highly with dietetic evaluations for assessing adherence (44) .…”
Section: Adherence Scoresmentioning
confidence: 99%
“…Currently, the Celiac Dietary Assessment tool (CDAT) is the most widely used scoring system. The CDAT is a seven-item questionnaire that has been used and validated in six studies to date, involving 1855 patients (35,44,(46)(47)(48)(49) . The CDAT has yet to be compared to histology for adherence but was found to correlate highly with dietetic evaluations for assessing adherence (44) .…”
Section: Adherence Scoresmentioning
confidence: 99%
“…In a study of biopsy-diagnosed CD patients, 40% of patients (n=164) agreed with the statement that it is difficult to find an RD knowledgeable about the GFD [12]. In a similar study which surveyed 160 biopsy-diagnosed CD patients, 54% of the participants (n=86) reported that RDNs did not seem to be knowledgeable about CD, and 53% of patients (n=85) did not find RDNs to be helpful [9].…”
Section: Discussionmentioning
confidence: 74%
“…Most all participants perceived a reduction in symptoms, a finding by others. [13,42] Slow diagnosis prolongs suffering for many affected individuals in some cases for many years (43). The limitations of a GFD would indicate that follow-up of affected individuals is important and medical professionals were consulted by all but 3 participants.…”
Section: Perceived Benefits Of Gfdmentioning
confidence: 99%